2020
DOI: 10.1073/pnas.2003496117
|View full text |Cite
|
Sign up to set email alerts
|

Vertical angular momentum constraint on lunar formation and orbital history

Abstract: The Moon likely formed in a giant impact that left behind a fast-rotating Earth, but the details are still uncertain. Here, we examine the implications of a constraint that has not been fully exploited: The component of the Earth–Moon system’s angular momentum that is perpendicular to the Earth’s orbital plane is nearly conserved in Earth–Moon history, except for possible intervals when the lunar orbit is in resonance with the Earth’s motion about the Sun. This condition sharply constrains the postimpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 29 publications
4
30
0
Order By: Relevance
“…So where does all this leave us? Well, the last major generalization of Laplace's work ushered a stream of applications, mainly to extra solar settings (Muñoz & Lai 2015;Zanazzi & Lai 2016), but also to scenarios of Lunar formation which argue for an initially steeply oblique and fast spinning Earth (Ćuk et al 2016;Tian & Wisdom 2020;Ćuk et al 2021). We can foresee the same for our renewed focus on the foundations of the Laplace Surface itself, and for the rich structure of equilibria we have identified, with applications ranging from man made satellites, to exo-moons around planets on Kozai-Lidov cycles, then debris disks with enclosed planets, the whole perturbed by a wide eccentric binary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So where does all this leave us? Well, the last major generalization of Laplace's work ushered a stream of applications, mainly to extra solar settings (Muñoz & Lai 2015;Zanazzi & Lai 2016), but also to scenarios of Lunar formation which argue for an initially steeply oblique and fast spinning Earth (Ćuk et al 2016;Tian & Wisdom 2020;Ćuk et al 2021). We can foresee the same for our renewed focus on the foundations of the Laplace Surface itself, and for the rich structure of equilibria we have identified, with applications ranging from man made satellites, to exo-moons around planets on Kozai-Lidov cycles, then debris disks with enclosed planets, the whole perturbed by a wide eccentric binary.…”
Section: Discussionmentioning
confidence: 99%
“…The circle was recently closed back onto the solar system, when it was realized that origin around a fast spinning and oblique Earth, which is favored on geochemical grounds, could generate a Moon whose Laplace plane may very well be prone to TTN's eccentricity instability! (Ćuk et al 2016;Tian & Wisdom 2020;Ćuk et al 2021) The present work begins where TTN left the Laplace Surface, and relaxes yet another assumption in the original Laplace story by explicitly accounting for an eccentric binary companion, thus effectively breaking the hitherto assumed axisymmetry of the outer perturber. This level of generality is again demanded by exo-planetary systems, the disks that generate them, remnant debris disks, all in the presence of a massive wide binary companion on an eccentric (and inclined) orbit.…”
Section: Introductionmentioning
confidence: 99%
“…During the instability, Earth's spin decreases and AM is transferred to Earth's orbit (Ćuk et al., 2016). However, Tian and Wisdom (2020) argue that such an evolution cannot reproduce the current Earth‐Moon system, because the needed initial high‐obliquity state is inconsistent with the component of the current Earth‐Moon angular momentum that is perpendicular to the ecliptic plane.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Recently, Tian & Wisdom (2020) have shown that the Laplace Plane instability, like other solar interactions with the Earth-Moon system, should conserve the component of the AM vector of the system that is perpendicular to the ecliptic (referred to by Tian & Wisdom (2020) as the "vertical AM" but which we will refer to as "ecliptic AM"). The simulations of Ćuk et al (2016) did not conserve this quantity, casting serious doubt on the results of Ćuk et al (2016), including the Earth-Moon system AM loss through the LPT.…”
Section: Introductionmentioning
confidence: 99%
“…The simulations of Ćuk et al (2016) did not conserve this quantity, casting serious doubt on the results of Ćuk et al (2016), including the Earth-Moon system AM loss through the LPT. Beyond the issue of ecliptic AM conservation, Tian & Wisdom (2020) stated that evolution through the Laplace Plane instability cannot result in the current Earth-Moon system regardless of the tidal parameters assumed for the system. Tian & Wisdom (2020) found that all high-obliquity Earth-Moon pairs with the correct ecliptic AM led to systems with too much AM and too high an obliquity for Earth at the end of the LPT.…”
Section: Introductionmentioning
confidence: 99%